Apoptotic Vesicles Attenuate Acute Lung Injury via CD73-Mediated Inhibition of Platelet Activation and NETosis - Tan L; Zhang C; Kou X; Zhao L; Wu D; Li J; Yu C; Xu T; Gao L; Mao X; Zhao C (International Journal of Nanomedicine)
Lingping Tan,1,2,* Chi Zhang,1,2,* Xiaoxing Kou,1– 3 Lu Zhao,4 Di Wu,1– 3 Jinyu Li,1,2 Chuanying Yu,1,2 Tansi Xu,1,2 Li Gao,1,2 Xueli Mao,1– 3 Chuanjiang Zhao1,2 1Hospital of Stomatology, Guanghua School of Stomatology, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Stomatology, Guangzhou, People’s Republic of China; 3South China Center of Craniofacial Stem Cell Research, Guangzhou, People’s Republic of China; 4Department of Orthodontics, Affiliated Stomatology Hospital of Guangzhou Medical University, Guangdong Engineering Research Center of Oral Restoration and Reconstruction, Guangzhou Key Laboratory of Basic and Applied Research of Oral Regenerative Medicine, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanjiang Zhao, Department of Periodontology, Hospital of Stomatology, Sun Yat-sen University, Guangzhou, Guangdong, 510055, People’s Republic of China, Email zhaochj@mail.sysu.edu.cn Xueli Mao, South China Center of Craniofacial Stem Cell Research, Guanghua School and Hospital of Stomatology, Sun Yat-sen University, Guangzhou, Guangdong, 510080, People’s Republic of China, Email maoxuel@mail.sysu.edu.cnIntroduction: Acute respiratory distress syndrome (ARDS) is a life-threatening type of acute lung injury (ALI) characterized by elevated mortality rates and long-term effects. To date, no pharmacological treatment has proven effective for ARDS. Mesenchymal stem cell-derived apoptotic vesicles (apoVs) were recently found to have excellent therapeutic potential for inflammatory diseases. In this study, our aim was to investigate the therapeutic effects and underlying mechanisms of apoVs in ALI.Methods: ALI was induced in mice through intratracheal instillation of lipopolysaccharide (LPS). ApoVs were then administered two hours post-induction, and their impacts on platelet activation, neutrophil infiltration, and NETosis were assessed. Additionally, the role of CD73 in mediating these effects was thoroughly investigated.Results: ApoVs inhibit platelet activation, thereby impeding the infiltration of neutrophils into the lung and the initiation of NETosis, ultimately alleviating ALI. Remarkably, apoVs were enriched with CD73, which was critical for apoV-mediated repression of platelet activation and neutrophil NETosis, as well as the therapeutic effects observed in lung injury.Conclusion: This study reveals that apoVs inhibit platelet activity and neutrophil NETosis via CD73, offering an innovative and effective cell-free therapeutic strategy for ALI/ARDS. Keywords: apoptotic vesicle, NETosis, platelet, ALI, CD73